Incidence of Bullying in Sparsely Populated Regions: An Exploratory Study in Ávila and Zamora (Spain) - María Nieto-Sobrino; David Díaz; Montfragüe García-Mateos; Álvaro Antón-Sancho; Diego Vergara (MDPI AG, 2023)
In this work, quantitative research on the incidence of bullying attitudes present among primary and secondary school students in a Spanish area with a very low population density (the one formed by the provinces of Avila and Zamora) was carried out. The data were obtained from a standardized test designed to diagnose bullying (AVE test: Acoso y Violencia Escolar-Bullying and School Violence), which was administered to a sample of 129 students between 9 and 15 years of age in the area. The answers of the participants were statistically analyzed, using both descriptive and inferential techniques, to conclude the degree of presence of the different bullying factors analyzed by the AVE. As a result, it can be observed that almost a quarter of the participants present were at risk of being bullied, which means that the rate of bullying in sparsely populated areas is below the national average. In addition, there are strong gender gaps in terms of the typology and incidence of bullying, which shows that men and women have different behaviors in this regard.